Вплив радіойоду на склад лімфоцитів крові хворих на рак щитоподібної залози молодого віку з віддаленими метастазами - Замотаєва, Г. А.; Степура, Н. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
The authors present the results of a study of phenotypic composition of blood lymphocytes in patients with differentiated thyroid cancer of young age before and after radioiodine therapy. A total of 50 patients with thyroid carcinoma have been followed up: 24 patients without distant metastases, 26 with distant metastases. Radioiodine activity received by the patients ranged from 3205 kBq to 6570 kBq. The control group consisted of 22 age-matched persons. Immunophenotype of peripheral blood lymphocytes was defined on the eve and 6 days after iodine-131 administration. The following changes in subpopulations' composition of peripheral blood lymphocytes at early periods after administration of therapeutic doses of radioiodine were noted in study patients: a significant decrease in Â-lymphocytes and immunoregulation index, a moderate growth in the content of subpopulations of suppressor/cytotoxic lymphocytes and regulatory T-cells, as well as an increased expression level of CD95+ and killer cells. It has also been demonstrated that in the course of radioiodine therapy the presence of distant metastases did not affect significantly subpopulations composition of peripheral blood lymphocytes the degree of immunologic disturbances.